The Effect of Mindfulness-Based Stress Reduction (MBSR) on Emotional Flexibility and Ambivalence Over Emotional Expression in Divorced Women: A Pilot Randomized Controlled Trial. Issue 4 (10th April 2023) - Heshmati, Rasoul; Khoury, Bassam; Azmoodeh, Shahin; Zerang, Masoumeh; Sadowski, Isabel
Abstract: The present study was developed to evaluate the effects of mindfulness-based stress reduction (MBSR) on the level of emotional flexibility and ambivalence related to emotional expression of divorced women. A general community sample of 30 divorced women was recruited and randomly assigned to experimental and control groups. The experimental group received MBSR for 8 weeks, and the control group was placed on a waiting list. The Emotional Flexibility Questionnaire (EFQ) and the Ambivalence Over the Expression of Emotion Questionnaire (AEQ) were administered to both groups before (pre) and after (post) the treatment. Data were analyzed using two-way mixed repeated-measures analyses of variance. The results showed that women in the treatment group had a significant increase in the total score of the EFQ and its components. In addition, the MBSR group had a significant decrease in the total score of the AEQ and its components. MBSR intervention shows potential for use with divorced women to help with emotion regulation and subsequent better adjustment to separation.